Antioxidant Synergy of Mitochondrial Phospholipase PNPLA8/iPLA2γ with Fatty Acid-Conducting SLC25 Gene Family Transporters - Jabůrek, Martin; Průchová, Pavla; Holendová, Blanka; Galkin, Alexander; Ježek, Petr (Antioxidants, 2021)
Patatin-like phospholipase domain-containing protein PNPLA8, also termed Ca2+-independent phospholipase A2γ (iPLA2γ), is addressed to the mitochondrial matrix (or peroxisomes), where it may manifest its unique activity to cleave phospholipid side-chains from both sn-1 and sn-2 positions, consequently releasing either saturated or unsaturated fatty acids (FAs), including oxidized FAs. Moreover, iPLA2γ is directly stimulated by H2O2 and, hence, is activated by redox signaling or oxidative stress. This redox activation permits the antioxidant synergy with mitochondrial uncoupling proteins (UCPs) or other SLC25 mitochondrial carrier family members by FA-mediated protonophoretic activity, termed mild uncoupling, that leads to diminishing of mitochondrial superoxide formation. This mechanism allows for the maintenance of the steady-state redox status of the cell. Besides the antioxidant role, we review the relations of iPLA2γ to lipid peroxidation since iPLA2γ is alternatively activated by cardiolipin hydroperoxides and hypothetically by structural alterations of lipid bilayer due to lipid peroxidation. Other iPLA2γ roles include the remodeling of mitochondrial (or peroxisomal) membranes and the generation of specific lipid second messengers. Thus, for example, during FA β-oxidation in pancreatic β-cells, H2O2-activated iPLA2γ supplies the GPR40 metabotropic FA receptor to amplify FA-stimulated insulin secretion. Cytoprotective roles of iPLA2γ in the heart and brain are also discussed.